"Law", "order", "justice", "crime": disrupting key concepts in criminology through the study of colonial history. Issue 4 (1st October 2020) - Moore, J.M.
ABSTRACT: This article reviews a final year undergraduate module, "Crime, Punishment and Justice in the British Empire", evaluating the extent to which it contributed a de/postcolonial perspective within the delivery of a criminology programme's curriculum. To do this the paper first critiques the discipline of criminology and its links with colonialism, before describing how this module was designed to address criminology's "colonial problem". The paper then explores the design and delivery of the module from the perspective of the author before providing a student perspective on the module based on data collected through five semi-structured interviews. The paper concludes that although the module largely met its objectives, a single option module can only have a limited impact. If criminology can be decolonised (something the paper remains agnostic about) it will require a radical rethinking of the curriculum at a programme level.